Sexual dimorphism in lung transcriptomic adaptations in fetal alcohol spectrum disorders - Vishal D. Naik; Dylan J. Millikin; Daniel Moussa; Hong Jiang; Alexander L. Carabulea; Joseph D. Janeski; Jiahui Ding; Kang Chen; Marta Rodriguez-Garcia; Sunil Jaiman; Stephen A. Krawetz; Gil Mor; et al. (Respiratory Research)
Abstract Current fetal alcohol spectrum disorders (FASD) studies primarily focus on alcohol’s actions on the fetal brain although respiratory infections are a leading cause of morbidity/mortality in newborns. The limited studies examining the pulmonary adaptations in FASD demonstrate decreased surfactant protein A and alveolar macrophage phagocytosis, impaired differentiation, and increased risk of Group B streptococcal pneumonia with no study examining sexual dimorphism in adaptations. We hypothesized that developmental alcohol exposure in pregnancy will lead to sexually dimorphic fetal lung morphological and immune adaptations. Pregnant rats were orogastrically treated once daily with alcohol (4.5 g/kg, gestational day [GD] 4 to 10, peak BAC, 216 mg/dl; 6.0 g/kg, GD 11 to 20, peak BAC, 289 mg/dl) or 50% maltose dextrin (isocalorically matched pair-fed controls) to control for calories derived from ethanol. Male and female fetal lung RNA from a total of 20 dams were assessed using the TapeStation (Agilent) and Qubit RNA broad-range assay. Samples with RNA Integrity Numbers (RINs) > 8 were prepared using the NEBNext Poly(A) mRNA Magnetic Isolation Module (NEB), xGen Broad-range RNA Library Prep (IDT), and xGen Normalase UDI Primer Plate 2 (IDT). Final libraries were checked for quality and quantity by Qubit hsDNA and LabChip. The samples were sequenced on the Illumina NovaSeq S4 Paired-end 150 bp. Fetal lung tissue were analyzed for histopathological assessments. Mean fetal weight, crown-rump length and placental efficiency of the alcohol-administered rats were significantly lower (P < 0.05) than the pair-fed control pups. Differentially expressed genes indicated a sex-linked gene regulation dichotomy with a significantly higher number of genes altered in the female fetal lungs compared to the male. Network analysis plot of downregulated genes in the females exposed to alcohol in utero showed a negative impact on T cell activation and regulation, T cell differentiation, decrease in CD8+ T cell number etc. The most altered genes were Cd8b, Ccl25, Cd3e, Cd27, Cd247, Cd3d, Ccr9, Cd2, Cd8a and were decreased by a log2fold change of > 2 (P < 0.05) in the female fetal lungs. KEGG analyses showed that male and female fetal lungs had downregulated genes associated with development and mitosis, whereas the females alone showed dysregulation of T cell genes. Comparison of gross appearance and histopathologic morphology showed that the developing lungs of both male and female fetal pups, displayed stunted differentiation, were relatively hypoplastic, and displayed a diminution of alveolar size and air spaces. Similarly, in both sexes, decreased alveolar capillarization was also evident in the alcohol-exposed fetal lungs. These data provide novel information in a growing area focused on alcohol effects on the offspring lung and its influence on appropriate fetal/neonatal immune responses and highlights the importance of examining sexual dimorphism in developmental adaptations.